Relationship between organizational climate and culture of patient safety in the health personnel of a national hospital of lima - Torres V., Manuel (2016)
The main purpose of the current investigation was to analyse the relationships that may exist between organizational climate and the culture of patient safety in a public hospital of Lima with the goal of generating viable alternatives that allow a significant improvement of the quality of attention to the patients that concur there. In the development of the current investigation were used the Scale of Organizational Climate (ECDO) of Acero Yusset and the Hospital Survey on Patient Safety in its Spanish version (Madrid: Ministry of Health and Consumption). The statistical analyses the tests were submitted to indicate us that the instruments are valid and reliable. These tests were applied to a sample of 155 people between doctors and nurses. The statistical results show us that the organizational climate and the culture of patient safety are significantly related; moreover, it was found that nurses value better the organizational climate and the culture of patient security than the doctors.